Boundedness of θ-Type Calderón–Zygmund Operators and Commutators in the Generalized Weighted Morrey Spaces. (31st October 2016) - Wang, Hua
Abstract : We first introduce some new Morrey type spaces containing generalized Morrey space and weighted Morrey space as special cases. Then, we discuss the strong-type and weak-type estimates for a class of Calderón–Zygmund type operators T θ in these new Morrey type spaces. Furthermore, the strong-type estimate and endpoint estimate of commutators [ b, T θ ] formed by b and T θ are established. Also, we study related problems about two-weight, weak-type inequalities for T θ and [ b, T θ ] in the Morrey type spaces and give partial results.